Digital Workout Versus Team Training: The Impact of the COVID-19 Pandemic on Athletes - Schneider, Friedemann; Runer, Armin; Burkert, Francesco; Aspang, Jesse Seilern Und; Reider, Simon; Schneider, Holm; Pocecco, Elena (Sports Medicine International Open, 2022)
The aim of the study was to assess the effects of the COVID-19 pandemic on sport practice and to identify measures adopted by individuals and sports organizations to allow a safe return to community sports. An electronic survey was launched worldwide in June 2020 in the German and English languages. The questionnaire collected anonymous data on sporting activity before, during, and after pandemic-induced confinement. Participants classified themselves as either recreational, competitive, or professional sports level athletes. A total of 1336 adults (30.5±11.7 years; 54.0% women) participated in the survey; 68.5% were active athletes, 10.1% coaches, 2.1% officials and 4.3% related medical staff, 3.6% had another function, and 11.4% indicated no regular sports activity. Most participants practiced their sport in Europe (93.8%); the majority (61.0%) was amateur athletes. During confinement, 15.7% could perform their main sport unrestricted, 43.5% stated a reduced amount of time spent on sporting activities, 46.4% a reduced intensity level. Most participants (77.5%) were neither aware of screening measures nor of guidelines for dealing with infected athletes (80.0%) or for return to sports after a coronavirus infection (88.6%). Preventive measures mentioned included basic hygiene, measures to reduce personal contacts or virus transmission, or to improve traceability of infections. During confinement, a higher age (p=0.004) and training in a club setting (p<0.001) were associated with reduced sporting activity, while the availability of online training (p=0.030) was linked to both increased extent and intensity levels. A lower age (p=0.001) and recreational sports level (p=0.005) were associated with decreased activity after confinement. Although isolation can be necessary to protect public health, it alters the amount and intensity of physical activity.
Keywords: COVID-19; pandemic; sports; physical activity; confinement; public health